Det er Herren, der styrer en mands gang - Siegismund , Kasper (Dansk Teologisk Tidsskrift, 2024)
This article discusses the question of agency in the Old Testament (OT) and challenges the view held by some scholars that the OT as a whole depicts human beings as having free will in the sense of being able to choose and having control over the choices they make. Many passages do seem to presuppose human choice and control, but the article presents numerous other passages that highlight God’s control of everything – including, in some cases, what human beings want and choose. Furthermore, several books of the OT describe the human ability to follow God’s commandments as deeply flawed and envisage a future divine intervention that will fundamentally change the way humans behave. Human free will must be understood in the light of this underlying notion of divine control that permeates the OT. However, this is not a fatalistic type of determinism. The tension between the notions of divine and human agency is real and both notions ought to inform our understanding of the theology of the texts.